(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Breast lesions constitute a common clinical problem and encompass a wide spectrum ranging from benign proliferative disorders to malignant neoplasms. Fine Needle Aspiration Cytology (FNAC) is a rapid, minimally invasive, and cost-effective diagnostic modality widely used in the initial evaluation of breast lumps. Cyto-histopathological correlation is essential to assess the diagnostic accuracy and reliability of FNAC. Aim and Objectives: To correlate the cytological findings of breast lesions with their histopathological diagnosis on excision and to evaluate the diagnostic accuracy of FNAC in breast lesions. Materials and Methods: This observational study was conducted in the Department of Pathology at M.P. Shah Medical College, Jamnagar, from April 2022 to August 2023. A total of 76 female patients presenting with breast lumps underwent FNAC followed by excision biopsy, lumpectomy, or mastectomy. Cytological reporting was performed according to NHS C1–C5 categories. Histopathological examination was carried out on formalin-fixed, paraffin-embedded tissue sections stained with Hematoxylin and Eosin. Cyto-histological correlation was performed, and diagnostic parameters including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy were calculated. Results: Among 76 cases, 36 (47.4%) were benign and 40 (52.6%) were malignant on histopathology. Fibroadenoma was the most common benign lesion (52.8% of benign cases), while infiltrating ductal carcinoma was the predominant malignant lesion (77.5% of malignant cases). Cytologically, 36 cases were categorized as C2, 1 as C3, and 39 as C5. One false-negative case was observed, and no false-positive cases were reported. FNAC demonstrated a sensitivity of 97.5%, specificity of 100%, PPV of 100%, NPV of 97.29%, and overall diagnostic accuracy of 98.68%. Conclusion: FNAC shows excellent diagnostic accuracy in the evaluation of breast lesions and serves as a reliable, rapid, and minimally invasive diagnostic tool. Proper sampling and standardized reporting enhance its effectiveness. Cyto-histopathological correlation remains essential to validate cytological findings and ensure optimal patient management.